Contribution of meals and snacks to nutrient intake of male and female elite figure skaters during peak competitive season. - Ziegler, P. J.; Jonnalagadda, S. S.; Nelson, J. A.; Lawrence, C.; Baciak, B. (Journal of the American College of Nutrition, 2002)
OBJECTIVE: To examine the contribution of breakfast, lunch, dinner and snack to the macronutrient and micronutrient intake of elite male and female figure skaters during their competitive season. SUBJECTS: Male (n = 46) and female (n = 48) figure skaters who participated in the 1999 U.S. National Figure Skating Championships completed the study. METHODS: Each athlete completed three-day food records, during the athlete's competitive season. Food records were analyzed using Nutritionist V software. Macronutrient and micronutrient contributions from meals were assessed. RESULTS: Lunch and dinner meals were the main contributors to the total calorie intake of these skaters (27% and 32%, respectively). Likewise, lunch and dinner were the main contributors to the total protein (27% and 41%), carbohydrate (26% and 29%), fat (30% and 32%), saturated fat (29% and 32%) and polyunsaturated fat (31% and 32%) intakes. Dinner was the main source of the monounsaturated fat (34%), cholesterol (40%) and dietary fiber (34%). Breakfast was the main source of dietary folate (36%), whereas iron and calcium intakes were mainly contributed by breakfast and dinner (29% and 32%, 27% and 29%, respectively). CONCLUSION: These elite figure skaters appear to be starting their day with low energy reserves and therefore need to be educated about the benefits of consuming breakfast. These athletes also need to be educated about consuming adequate calories throughout the day in order to meet the energy needs of their activity. It is thus important to monitor eating patterns throughout the day to ensure adequate energy intake to sustain the physical and mental aspects of the athletes' training and performance.